Performance enhancement of organic single-flash cycles by eliminating the throttle valves: A comparative exergy-economic assessment - Aboulbaba Eladeb; Ali B.M. Ali; Pooya Ghodratallah; Kuwar Mausam; Rahul Thakur; Praney Madan; Lotfi Ben Said; Lioua Kolsi (Case Studies in Thermal Engineering)
The excessive energy and exergy wastage resulting from the throttling processes in flash-based cycles is a significant concern. Researchers have proposed several solutions to mitigate these negative impacts. Nevertheless, there has been limited focus on comparing these solutions. The present study is carried out to compare the thermo-economic performances of five organic cycles driven by a geothermal heat source. The configurations are an organic Rankine cycle (ORC), an organic flash cycle (OFC), a modified organic flash cycle (MOFC), an organic flash regenerative cycle (OFRC), and a modified organic flash regenerative cycle (MOFRC). The five configurations are compared in the optimum operating conditions considering the exergy efficiency (ηex) and the unit cost of electricity generation (cel) as the determinant parameters. The MOFC and MOFRC demonstrate a significant enhancement in ηex, with an improvement of 10.94 % points and 5.6 % points, respectively, compared to the OFC and OFRC. Furthermore, ηex of the OFRC and MOFRC exhibits an improvement, with values 9.15 % points and 3.81 % points higher than those of the OFC and MOFC, respectively. Notably, the basic ORC has the highest ηex equal to 54.26 %. However, its investment cost rate (Z˙tot) is 8 % higher than the MOFRC. In addition, the MOFRC, with an ηex and cel of 51.8 % and 6.87 $GJ−1, has a competitive performance compared to the ORC. A comprehensive comparison between the MOFRC and previous configurations based on the flash process indicates that the MOFRC has the highest ηex and lowest cel among the configurations.